Artificiality in Sunnah and Scholars contribution to prevent it - Hafiz, Uddin; Gias, Md (IIUC Studies, 2009)
The full text of this article is in Arabic - see PDF below. doi: 10.3329/iiucs.v4i0.2860 IIUC STUDIES Vol. - 4, December 2007 (p 33-44).